2016
DOI: 10.3389/fmicb.2016.01354
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of the Vancomycin Resistance Genes vanA and vanC of Enterococcus Isolated from Nile Tilapia on Retail Sale: A Public Health Hazard

Abstract: Although normally regarded harmless commensals, enterococci may cause a range of different infections in humans, including urinary tract infections, sepsis, and endocarditis. The acquisition of vancomycin resistance by enterococci (VRE) has seriously affected the treatment and infection control of these organisms. VRE are frequently resistant to all antibiotics that are effective treatment for vancomycin-susceptible enterococci, which leaves clinicians treating VRE infections with limited therapeutic options. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…With regard to the pathogenicity test, the clinical signs in our results appeared within 14 days after intraperitoneal injection of O. niloticus by E. faecalis , which resulted in 91.66% morbidity and 83.33% mortality. This finding was nearly identical to the results of Osman et al (2016), who recorded 100% mortality in O. niloticus 6 days of injection with E. faecalis . In our study, fish injected with A. viridans showed a mortality of 91.66%, which is in close agreement with the study by Ke et al (2012), who recorded 85% mortality within 14 days postinjection with the same bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…With regard to the pathogenicity test, the clinical signs in our results appeared within 14 days after intraperitoneal injection of O. niloticus by E. faecalis , which resulted in 91.66% morbidity and 83.33% mortality. This finding was nearly identical to the results of Osman et al (2016), who recorded 100% mortality in O. niloticus 6 days of injection with E. faecalis . In our study, fish injected with A. viridans showed a mortality of 91.66%, which is in close agreement with the study by Ke et al (2012), who recorded 85% mortality within 14 days postinjection with the same bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…isolated from chicken, ducks, pigs, fish, and raw milk cheese. VanA ( n = 23), vanB ( n = 27), vanC ( n = 38), and tet (M) ( n = 6) were the dominant resistance genes; Tn 916 ( n = 7) was the MGE detected.…”
Section: Resultsmentioning
confidence: 99%
“…Chajecka-Wierzchowska et al (2016) also reported the presence of vanC2/3 genes in E. casseliflavus isolates from ready-to-eat meat products but not vanC1 gene. Moreover, a study in Egypt demonstrated vanC gene carrying E. gallinarum and E. faecalis strains from fish samples (Osman et al, 2016). Conversely, lack of vanC gene in animal originated food was recently reported by Yilmaz et al (2016) in Turkey and by Gousia et al (2015) in Greece.…”
Section: Discussionmentioning
confidence: 97%
“…Another work revealed the presence of vanA gene in three vancomycin-susceptible E. faecalis isolates and one E. hirae isolate (Perin et al 2014). Osman et al (2016) and Harada et al (2012) detected vanA gene in one E. faecalis strain from fish and one E. cecorum strain from poultry samples, respectively. Contrary results were reported by Kasımoğlu-Doğru et al (2010) and Chajecka-Wierzchowska et al (2016).…”
Section: Discussionmentioning
confidence: 98%